Agreement and reliability analysis of cytological and histopathological diagnoses of cutaneous and subcutaneous neoplasms in 27 dogs treated in Caxias do Sul, Rio Grande do Sul (Research, Society and Development, 2025)
Cutaneous and subcutaneous neoplasms represent about 30% of tumor diagnoses in dogs. Due to their atypical morphology, microscopic identification is indispensable. Cytopathology assists in differentiating inflammatory from neoplastic processes; however, the definitive diagnosis depends on histopathological examination, considered the gold standard. This study aimed to compare cytopathological and histopathological results of cutaneous and subcutaneous tumors in dogs treated at a veterinary clinic in Caxias do Sul, between January 2019 and December 2021, evaluating cell origin, biological behavior, and reliability between the methods. A total of 27 medical records of dogs with a final diagnosis of cutaneous and subcutaneous neoplasms and both exams available were reviewed. The cases were analyzed according to cell origin and diagnosis, establishing agreement rates and reliability between cytopathology (CT) and histopathology (HT). For this purpose, neoplasms were grouped into malignant and benign, and the Kappa test was applied. The coefficient obtained was 0.632, with 85.7% agreement, indicating moderate reliability between the methods for detecting malignancy. Round cells showed the highest degree of agreement, and mast cell tumor was the most frequent neoplasm. It is concluded that CT is effective as a suggestive diagnostic tool, but it cannot replace HT, which remains indispensable for diagnostic confirmation.